Effectiveness of Some Ameliorants in Reducing Co2 and N2o Emission in Corn Planting in Peat Land - Eni Maftuah; R S Simatupang; Herman Subagyo; Dedi Nursyamsi (Journal of Wetlands Environmental Management, 2016)
Amelioration is very important in supporting plant growth in peat land. The use of low emission ameliorant will support the sustainability of agricultural system in peat land. The research is intended to study the effectiveness of some ameliorants in reducing CO2 and N2O emission in corn planting in peat land. The research was conducted in April to October 2013, in Kalampangan Village Palangkaraya Municipality Central Kalimantan. Ameliorant materials used were chicken manure fertilizer, domolite, mineral soil, paddy husk biochar, coconut shell biochar. Ameliorant treatments applied were the type of ameliorant compositions, those were (A1) 80% chicken manure fertilizer + 20% dolomite, (A2) 20% chicken manure fertilizer + 20% agricultural weeds + 20% spodosol mineral soil + 20% â€œpurun tikusâ€ (eleocharis dulcis) compost + 20% dolomite, (A3) 19% chicken manure fertilizer + 9% dolomite + 72% mineral soil, (A4) 100% coconut shell biochar, (A5) paddy husk biochar, (A6) farmerâ€™s way (20% ash + 40% spodosol mineral soil + 40% chicken manure fertilizer) and control. Experiment design used a Randomized Factorial Block Design, with 3 repetitions. Ameliorant dosage used was 7.5 t/ha. The crop used was hybrid corn. Parameters which were observed periodically were emission of CO2 and N2O, ground water level height, soil pH and Eh, once a month for 5 periods. The research result showed that ameliorant was capable of reducing emission of both CO2 and N2O in corn planting in peat land. Coconut shell biochar could reduce emission of CO2 up to 26% as compared with control, whereas paddy husk biochar could reduce emission of N2O up to 52% as compared with control.